2003
DOI: 10.1310/f2v7-3r46-vx6j-241r
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Changes in Patients Initiating Efavirenz- and Indinavir-Based Antiretroviral Regimens

Abstract: EFV and IDV independently elevate lipid levels. Alterations in the lipid levels may lead to increased cardiovascular risk in men, possibly mitigated by elevations in HDL cholesterol. In addition, changes in HDL cholesterol were significantly different between men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…But also patients with a normal HDL-c level, who are not at an increased CHD risk, showed marked increases in HDL-c. This baseline effect can likewise be distilled from the other studies, where those with the lowest baseline value (0.93 mmol/l; Atlantic study [12]) showed the largest HCL-c increase, while the smallest increase was seen in the study with the highest baseline value (1.23 mmol/l; Tashima study [13]). The study by Negredo et al [21], which included patients with similar baseline HDL-c levels as in the present study, showed an increase of HDL-c comparable to that in the present study (0.34 and 0.36 mmol/l, respectively).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…But also patients with a normal HDL-c level, who are not at an increased CHD risk, showed marked increases in HDL-c. This baseline effect can likewise be distilled from the other studies, where those with the lowest baseline value (0.93 mmol/l; Atlantic study [12]) showed the largest HCL-c increase, while the smallest increase was seen in the study with the highest baseline value (1.23 mmol/l; Tashima study [13]). The study by Negredo et al [21], which included patients with similar baseline HDL-c levels as in the present study, showed an increase of HDL-c comparable to that in the present study (0.34 and 0.36 mmol/l, respectively).…”
Section: Discussionmentioning
confidence: 88%
“…Van der Valk et al reported an increase of HDL-c of 0.44 mmol/l for patients initiating treatment with didanosine, d4T, and NVP in the Atlantic trial [12]. Tashima et al reported an increase of HDL-c of 0.21 mmol/l in patients treated with EFV and either zidovudine plus 3TC, or indinavir [13], while Negredo et al showed an increased HDL-c concentration in therapy-naive patients starting a regimen of didanosine, d4T, and EFV (0.34 mmol/l) [22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have implicated efavirenz in worsening of lipid parameters (96). When combination drugs are created, adverse effects on metabolic indices could be amplified or attenuated due to the combined individual effects of each individual drug component.…”
Section: Multi-class Drug Combinationsmentioning
confidence: 99%
“…Many antiretroviral regimens, including EFV, are related to adverse effects in serum lipids. This often necessitates lipid-lowering treatment ( 28 , 29 ). Multiple studies have shown that EFV demonstrate more negative changes in TC, TG, and LDL-C than elvitegravir (EVG) ( 30 32 ), raltegravir (RAL) ( 33 , 34 ), dolutegravir (DTG) ( 35 ), nevirapine (NVP) ( 36 ), and rilpivirine (RPV) ( 37 ) when used in people with HIV-1.…”
Section: Discussionmentioning
confidence: 99%